Cyber Konseling: Sebuah Model Konseling Pada Konteks Masyarakat Berbasis Online - Bastomi, Hasan (Konseling Edukasi : Journal of Guidance and Counseling, 2019)
Cyber Counselling: A Model of Counselling in the Online-Based Society Context. A decade lately the virtual world appears to be one of the most important aspect in human life. Virtual reality, one of which developed from the evolution of the internet creates a virtual space that can be a representation or simulation of real life, including in the field of guidance and counselling called cyber counselling. Cyber counselling services are one of the virtual counselling service strategies or counselling that takes place by using an internet connection. Cyber Counselling is the alternative way when today, almost everyone who has a smartphone, also has social media accounts, such as Facebook, Twitter, Path, Instagram, and so on. Nevertheless, the counselling process can occur separately between counsellors and counselees in different time and place. In implementing cyber counselling a number of issues such as ethical issues and issues of developing counselling relationship may arise and must be considered. Therefore, cyber counsellors should have the ability of cyber counselling.